Climate Warming: Is There Evidence in Africa? - Hector Carcel; Luis A. Gil-Alana (Advances in Meteorology)
We have examined the temperature time series across several locations in Africa. In particular, we focus on three countries, South Africa, Kenya, and Côte d’Ivoire, examining the monthly averaged temperatures from three weather stations at different locations in each country. We examine the presence of deterministic trends in the series in order to check if the hypothesis of warming trends for these countries holds; however, instead of using conventional approaches based on stationary I(0) errors, we allow for fractional integration, which seems to be a more plausible approach in this context. Our results indicate that temperatures have only significantly increased during the last 30 years for the case of Kenya.